Elastic Electron Scattering form Factors for Odd-A 2s-1d Shell Nuclei - Majeed Al-Rahmani, Altaf Abdul; Aljabbar Hussein, Huda Abd (Iraqi Journal of Science, 2023)
The charge density distributions (CDD) and the elastic electron scattering formfactors F(q) of the ground state for some odd mass nuclei in the 2s 1d shell, suchas K Mg Al Si 19 25 27 29 , , , and P 31have been calculated based on the use ofoccupation numbers of the states and the single particle wave functions of theharmonic oscillator potential with size parameters chosen to reproduce the observedroot mean square charge radii for all considered nuclei. It is found that introducingadditional parameters, namely; 1  , and , 2  which reflect the difference of theoccupation numbers of the states from the prediction of the simple shell model leadsto very good agreement between the calculated and experimental results of thecharge density distributions throughout the whole range of r.The experimentalelectron scattering form factors for K Mg Al Si 19 25 27 29 , , , and P 31nuclei are inreasonable agreement with the present calculations throughout all values ofmomentum transfer q.